Penerapan Metode Prototype Dalam Perancangan Sistem Informasi Service Pada Bengkel Sido Motor Berbasis Website - Vembria Rose Handayani; Meida Intan Saputri; Eka Rahmawati; Chandra Kesuma (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2024)
Abstracts - Motorbikes, as private vehicles, are an economical and very popular means of transportation in Indonesia. However, almost all motorbike riders have experienced problems such as a loose or broken chain, engine breaking down, and other problems. For this reason, workshops have an important role in helping motorists overcome these various problems. Sido Motor Workshop is one of the workshops located in Karangsalam Village, Kemranjen, Banyumas. Sido Motor Workshop provides service services, sells spare parts, oil and a variety of other motorbikes. Service at the Sido Motor workshop is still manual. This means that customers have to queue if they want to get motorbike service. Processing transaction data and payments for services, spare parts and preparing reports is still done manually. Therefore, it is necessary to design an information system to facilitate service activities at the Sido Motor workshop. The method for designing this information system uses the prototype method, where this method has stages, namely requirements gathering and system analysis, design modeling, prototype formation, and prototype evaluation. Using UML to describe the flow and functionality of a system. It is hoped that the implementation of the information system at the Sido Motor workshop will make all activities more effective and efficient. Admins can manage service data and make reports in a timely manner. And the Sido Motor workshop's income continues to increase and the number of customers continues to increase.